2000
DOI: 10.1055/s-2000-3748
|View full text |Cite
|
Sign up to set email alerts
|

Erste Erfahrungen mit einem neuen optischen Zielsystem (SimpliCT) für CT-gesteuerte Punktionen

Abstract: The laser target device is a simple navigation system which allows accurate positioning of a needle. Requiring an acceptable low preparation time, it easily can be integrated into the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…The results from one of the centers have been published in two preliminary reports (7,8) and the data are included in this study. With 84.6% of the lesions hit on the first needle pass and a mean needle deviation of 1.8 ‡ we found that by using the laser guide different users at four European centers obtained a high and consistent level of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The results from one of the centers have been published in two preliminary reports (7,8) and the data are included in this study. With 84.6% of the lesions hit on the first needle pass and a mean needle deviation of 1.8 ‡ we found that by using the laser guide different users at four European centers obtained a high and consistent level of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Alternativ kann auch durch den Einsatz von optischen oder lasergestützten Systemen wie SimpliCT oder LZH (LasermarkierungsZiel-Hilfe) eine wesentliche Arbeitserleichterung erreicht werden, indem die Anzahl der Kontrollschnitte und die Dauer der Punktion gerade für den ungeübten Punkteur herabgesetzt wür-den [23,24]. Zusätzlich kann bei der SimpliCT-Methode die Punktion auch mit gekippter CT-Gantry durchgeführt werden.…”
Section: Materials Und Methodeunclassified
“…Diese ist einfach, sicher und kosteneffizient durchzuführen [4,5,16], neueste Entwicklungen erhöhen die Sicherheit [17]. Für zentrale Läsionen sind in Einzelfällen Kombinationen der CT-Führung mit der Bronchoskopie beschrieben [18].…”
Section: Diskussionunclassified